Semangat Kerja Sama dan Gotong Royong di Kalangan Masyarakat - Ayu Nurani Az Lubis (PT. Willy Print Art, 2025)
This study examines the spirit of cooperation and mutual assistance as fundamental social values that shape community cohesion and collective resilience. Cooperation and gotong royong have long been embedded in Indonesian society, functioning as moral foundations that encourage solidarity, shared responsibility, and participatory engagement in social life. This research aims to analyze the relevance of these values in contemporary society, particularly in the face of modernization, individualism, and social change. Using a qualitative descriptive approach, data were collected through literature review and analysis of social practices within communities. The findings indicate that the spirit of cooperation and gotong royong remains highly relevant as a means of strengthening social harmony, enhancing collective problem-solving, and fostering a sense of belonging among community members. However, challenges such as declining social interaction and the rise of self-centered attitudes have weakened these values in certain contexts. Therefore, revitalizing cooperation and mutual assistance through education, cultural preservation, and community-based programs is essential to ensure their sustainability. Strengthening these values contributes not only to social stability but also to the development of inclusive and resilient communities.